Loose lips - Donovan, Kemper (Donovan, Kemper. Ghostwriter mystery, 2025)
A successful ghostwriter reluctantly joins the "Get Lit Cruise" hosted by her frenemy Payton Garrett, but the event turns deadly when an attendee is murdered and others fall ill, prompting her to navigate a web of motives and suspects while grappling with her past and chaotic cruise dynamics.